2020
DOI: 10.1177/1474515120951974
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver experiences of paediatric inpatient cardiac services: A qualitative systematic review

Abstract: Background: Advances in paediatric care have contributed to an increasing survival of children with complex heart disease. Yet, life-saving management demands prolonged inpatient admissions, which contribute to emotional and psychological distress for parents and other caregivers in a role of main custody. Aim: The purpose of this study was to identify, appraise and synthesise qualitative studies exploring caregivers’ experiences of paediatric inpatient cardiac services, generating an understanding of their ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Previous studies have shown that parents of children with CHD as their main caregivers require an individualized and multidisciplinary approach toward care to best adapt to the dynamic stressors associated with raising a child (Gramszlo et al, 2020). Emotional challenges related to being a caregiver of a child with CHD and/or other cardiac diseases (OCD) affect caregivers' competence, well-being, and attachment to sick children (Knight Lozano et al, 2021). The literature on the subject has focused mainly on qualitative research on the functioning of parents/guardians of children with CHD and other OCD (Hoffman et al, 2020;Landry et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that parents of children with CHD as their main caregivers require an individualized and multidisciplinary approach toward care to best adapt to the dynamic stressors associated with raising a child (Gramszlo et al, 2020). Emotional challenges related to being a caregiver of a child with CHD and/or other cardiac diseases (OCD) affect caregivers' competence, well-being, and attachment to sick children (Knight Lozano et al, 2021). The literature on the subject has focused mainly on qualitative research on the functioning of parents/guardians of children with CHD and other OCD (Hoffman et al, 2020;Landry et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Family and caregivers with such complex cardiovascular diseases are emotionally and psychologically affected; this influences their care, behaviors, and attitudes. Specifically speaking, the emotional challenges that caregivers face and the practicalities of undertaking the role of a caregiver has an impact on both the caregiver and the QoL of the patient [ 12 ]. Most commonly, care provided by the caregivers can be experienced as being stressful.…”
Section: Introductionmentioning
confidence: 99%
“…Although surgical techniques for congenital heart disease (CHD) have improved in recent years, up to 50% of mothers experience significant depression and anxiety before and after surgery. [1][2] Mothers of children undergoing cardiac surgery appear to experience greater anxiety than those whose children undergo other types of surgeries. 3 Additionally, surgical or post-surgical complications could exacerbate maternal depression and anxiety.…”
Section: Introductionmentioning
confidence: 99%